Suppression of TNBS-induced colitis in rats by 4-methylesculetin, a natural coumarin: Comparison with prednisolone and sulphasalazine - Witaicenis, Aline; Luchini, Ana C.; Hiruma-Lima, Clélia Akiko [UNESP]; Felisbino, Sergio L. [UNESP]; Garrido-Mesa, Natividad; Utrilla, Pilar; Galvez, Julio; Di Stasi, Luiz C. [UNESP] (Elsevier B.V., 2012)
The aim of the present study was to compare the effects of the 4-methylesculetin with those produced by prednisolone and sulphasalazine and to elucidate the mechanisms involved in its action. Colitis was induced in rat by instillation of trinitrobenzenesulphonic acid (TNBS). The colon damage was evaluated using macroscopic, microscopic and biochemical analysis. In addition, in vitro studies were performed to evaluate cytokine production in cell cultures using the murine macrophage cell line RAW264.7, mouse splenocytes and the human colonic epithelial cell line Caco-2. 4-Methylesculetin produced a reduction of the macroscopic damage score and the recovery of the intestinal cytoarchitecture. These effects were associated with a prevention of the GSH depletion and an inhibition in AP activity. After colitis relapse, 4-methylesculetin improved the colonic inflammatory status as evidenced by histological findings, with a reduction in apoptosis, as well as biochemically by inhibition of colonic myeloperoxidase, alkaline phosphatase and metalloproteinase 9 activities. Paired with this inhibitive activity, there was a decrease in malondialdehyde content and in IL-1 beta levels. In vitro assays revealed that 4-methylesculetin promoted an inhibition in IL-1 beta, IL-8, IL-2 and IFN-gamma production in cell cultures. In conclusion, 4-methylesculetin showed similar efficacy to that obtained with either prednisolone or sulphasalazine, both in the acute phase of colitis as well as following a curative protocol. The intestinal anti-inflammatory activity by 4-methylesculetin is likely related to its ability in reduce colonic oxidative stress and inhibit pro-inflammatory cytokine production. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: IBD; 4-Methylesculetin; TNBS; Metalloproteinase; Apoptosis